Environmental Impact Assessment (EIA) of the Proposed Leuwikeris Dam Construction in Ciamis and Tasikmalaya Regencies, West Java Province - Agus Irpan Nurhidayat (INTERDISIPLIN: Journal of Qualitative and Quantitative Research, 2026)
This study analyzes the environmental impacts of the Leuwikeris Dam construction in Tasikmalaya and Ciamis Regencies, West Java—a multipurpose national strategic project. Employing an in-depth literature review of official Environmental Impact Assessment (AMDAL) documents (ANDAL, RKL-RPL, KA-ANDAL), government reports (2021–2025), scientific journals, and recent secondary data, the study identified 28 hypothetical significant impacts using a modified Leopold matrix. The results indicate highly positive benefits, including an 11.7% reduction in flooding, irrigation for 11,216 hectares, a raw water supply of 845 L/second, and a combined hydropower potential (PLTA and PLTM) of 27.4 MW. However, significant negative post-operational impacts (post-2025) were identified, such as the accumulation of domestic waste, water hyacinth proliferation (covering >40% of the reservoir surface), annual sedimentation of 4.8 million m³, and unresolved social conflicts regarding land acquisition. The study concludes that the Leuwikeris Dam project remains sustainable provided the Environmental Management and Monitoring Plan (RKL-RPL) is revised via a 2026 addendum to incorporate waste management programs, water hyacinth bioremediation, and community-based tourism development. This research contributes data-driven policy recommendations that can serve as a reference for managing similar dam projects in Indonesia.